ANALISIS AKUNTABILITAS, TRANSPARANSI, DAN EFEKTIVITAS PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) PADA MASA COVID19 TERHADAP PENCAPAIAN GOOD GOVERNANCE (Studi Empiris di Desa Bendosari, Kec Sawit, Kab Boyolali) - Putri Nur Azizah; Sri Laksmi Pardanawati; LMS Kristiyanti (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to determine the effect of: 1) accountability, 2) transparency, and 3) effectivity of village direct cash assistance on achievement of good governance. The sampling technique in this study used a purposive sampling and get 50 samples. In this study the researcher used primary data with the descriptive analysis method, validity test, reliability test, classical assumption tests, multiple linear regression analysis, f test, t test, and the determination coefficient test with the help of the SPSS version 21. The result show that accountability of village direct cash assistance has a significant effect on the achievement of good governance, tranparency of village direct cash assistance has a significant effect on the achievement of good governance, effectivity of village direct cash assistance has a significant effect on the achievement of good governance. Keywords : accountability, transparency, effectivity, village direct cash assistance, good governance.